Draft Genome Sequence of the Cellulolytic Bacterium Clavibacter sp. CF11, a Strain Producing Cold-Active Cellulase - Du, Ying; Yuan, Bo; Zeng, Yonghui; Meng, Jianyu; Li, Heng; Wang, Ruigang; Li, Guojing; Feng, Fuying (Genome announcements, 2015)
Clavibacter sp. strain CF11, which was isolated from soil at a tomato-planting greenhouse in Inner Mongolia, North China, has a high capability for producing cold-active cellulase at low temperatures. Here, we report the draft genome sequence of strain CF11, which comprises 2,437 protein-coding sequences and 49 RNA-coding sequences.